Market Orientation, Generative Learning, Innovation Strategy and Business Performance Inter‐Relationships in Bioscience Firms - Morgan, Robert E.; Berthon, Pierre (Journal of Management Studies, 2008)
abstractWe propose conceptual arguments to establish relationships between market orientation and generative learning and their respective impact on exploitative innovation strategy and explorative innovation strategy. We then consider the ambidextrous association between both forms of innovation strategy and business performance. This model is subject to an empirical test using data generated from 160 bioscience firms. Using structural equation modelling, two mutually exclusive paths are specified where market orientation leads to exploitative innovation strategy, while generative learning leads to explorative innovation strategy. We then find that the ambidexterity exhibited by firms in the form of exploitative innovation strategy and explorative innovation strategy significantly explains improvements in firms’ business performance. Discussion is given to these findings and managerial implications are presented along with avenues for further research.